المحمدية سوميدانج SMK 1تطوير مواد تدريس الكتب المدرسية حول المواد الإسلامية الوسطية في - Supala (Yayasan Mentari Madani, 2023)
The foundation of Wasatiyah values in Islam is very strong, as evidenced by QS Al-Baqarah (2): 143 which aims to instill mercy for all aspects of nature, and QS Al-Anbiya (21): 107 which emphasizes the concept of every human being as Abdullah and Khalifatullah. The purpose of this study is to determine the development of textbook teaching materials on wasathiyah Islamic material. This writing method uses literature research. That is, it is focused on the exploration and analysis of data derived from written documents, or texts. All data used to conduct research is sourced from texts or manuscripts that are part of the library's collection. The results of this study show that there is a teaching of intolerance in PAI textbooks delivered in the form of blaming different opinions or worship practices, the State does not make the production of PAI textbooks part of national cultural politics for the development of national character. There is a lack of decision on the vision, mission, and goals of the PAI textbooks, so that it does not contain the teachings and messages of Islam that rahmatan lil 'alamiin is appropriate with Indonesian national values